Social support and associated factors among family caregivers of older people in North-East Peninsular Malaysia - Aniawanis Makhtar; Nor Nadiya Ab Ghani; Sharifah Munirah Syed Elias; Salizar Mohamed Ludin (Belitung Raya Foundation, Indonesia, 2023)
Background: The negative health results associated with the family caregivers of older people can be alleviated with social support, which is considered a valuable resource. Hence, the factors contributing to social support need to be understood. Objective: This study aimed to evaluate the social support associated with the family caregivers of older people. Methods: A cross-sectional study was conducted among 231 family caregivers of older people conveniently selected from two districts in Kelantan, a state in the North-East Region of Peninsular Malaysia. Data were gathered between June to December 2021 using a Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire. Descriptive statistics were used to summarize the data in frequencies and percentages. Independent t-test and one-way analysis of variance were used to examine correlations among variables. Results: The mean scores of social support for family caregivers were significantly higher among their family (Mean ± SD; 5.44 ± 0.969) and other important people (5.25 ± 1.123) compared to their friends (4.84 ± 1.094). Caregivers’ gender and duration of caregiving were significant factors associated with social support (p <0.05). Conclusions: The family caregivers received maximum support from their family and other important people, but they were less supported by their friends. This study also observed that the perceived social support of the caregivers of older people was affected by several factors, such as gender and duration of caregiving. This finding gives nurses and other healthcare workers the basic information they need to enhance nursing interventions and promote social support among those who care for older people, which can positively impact caregiving.